2014
DOI: 10.1002/joc.4042
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of rainfall in four meteorological subdivisions of southern India using nonparametric methods and discrete wavelet transforms

Abstract: In recent times, trend analysis and change point detection in hydroclimatic variables receiving significant attention due to climate change and its socioeconomic consequences. In this study, long‐term trends of rainfall in four subdivisions of southern India namely Kerala, Tamil Nadu, North Interior (NI) Karnataka and Telangana regions are analysed using linear regression, nonparametric Mann–Kendall (MK) test and Sen's slope estimator methods. Trend analysis of annual rainfall time series shows an increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 57 publications
0
55
0
Order By: Relevance
“…The SQMK test estimates a sequence of MK values (for different time instants), and the intersection of progressive and retrograde series indicates a trend turning point. More details of this test can be found elsewhere (Adarsh & Janga Reddy, ; Gerstengarbe & Werner, ; Modarres & Sarhadi, ). The results of SQMK test of the SPI3 series for the three subdivisions are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SQMK test estimates a sequence of MK values (for different time instants), and the intersection of progressive and retrograde series indicates a trend turning point. More details of this test can be found elsewhere (Adarsh & Janga Reddy, ; Gerstengarbe & Werner, ; Modarres & Sarhadi, ). The results of SQMK test of the SPI3 series for the three subdivisions are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The monthly rainfall data of Kerala, Telangana, and Orissa subdivisions for the period 1871–2012 was collected from Indian Institute of Tropical Meteorology Pune (htpp://http://www.tropmet.res.in) and used for determining SPI3 values of the three regions. In the past, several researchers have used these datasets for spatio‐temporal trend analysis of rainfall and droughts over different regions in India (Adarsh & Janga Reddy, ; Ganguli & Janga Reddy, ; Joshi et al, ; Thomas & Prasannakumar, ). The time series of the monthly rainfall data of the three subdivisions are presented in Figure .…”
Section: Study Area and Datasetsmentioning
confidence: 99%
“…In the past, several studies conducted to analyze the rainfall trends over different regions of India (Mohapatra et al 2003;Kumar et al 2010;Krishnakumar et al 2009;Jain et al 2013;Adarsh and Janga Reddy 2015a). Few studies also dealt with the characterization and forecasting of monsoon rainfall over India (Walker 1933;Shukla and Paolino 1983;Kripalani and Kulkarni 1997;Bhattcharya and Narasimha 2007).…”
Section: Related Workmentioning
confidence: 97%
“…moisture, and groundwater reserves (Jain et al 2013;Adarsh and Janga Reddy 2015a). In recent past, several studies reported that climate is changing with warming of the atmosphere and ocean system, and resulting in changes in rainfall amounts and hydrological extremes and causing increase of floods and droughts worldwide (IPCC 2007).…”
mentioning
confidence: 99%
“…Wavelet analysis has been extensively employed to determine the non-stationary trends and periodicities in the analysis of various hydrological and meteorological variables [34][35][36][37]. In order to better analyze the trends and the fluctuating patterns of the hydrological variables, the wavelet transform has been recently used in conjunction with the MK test [20,[38][39][40]. Partal and Küçük (2006) [22] firstly co-utilized the wavelet transform and the original MK test to find which periodicities are mainly responsible for the trends of the annual total precipitation series and found that the trend analysis on detailed components of the precipitation time series resulting from the discrete wavelet transform (DWT) can clearly explain the trend structure of data.…”
Section: Introductionmentioning
confidence: 99%